Hasil Tangkapan Ikan Pelagis Pada Perikanan Purse Seine Hubungannya Dengan Parameter Oseanografi Di Perairan Selat Makassar Kabupaten Tolitoli - Iriani, Novita Dewi; Masyahoro, A.; Laapo, Alimudin (Universitas Tadulako, 2023)
This research aims to analyze oceanographic parameters and the number of pelagic fish caught in purse seine fisheries in the Makassar Strait, Toli-Toli Regency. The research was carried out using purposive sampling with purse seine catch data collected at 30 FADs (as research sites). Oceanographic data includes sea surface temperature, currents, pH, dissolved oxygen, and waves collected in situ. Meanwhile, nitrate and phosphate samples were analyzed at the Agricultural Science Study Program Laboratory, Tadulako University. Results of analysis of the composition of pelagic fish species caught in purse seine catches in February 2021 (4 types of fish are classified as economically important fish and the other three types are by-catch). In order of highest catches, they were kites (18,632 kg; 24 FADs), skipjack (15,203 kg; 27 FADs), tuna (4,290 kg; 12 FADs), mackerel tuna (3,060 kg; 4 FADs), tuna (4,500 kg; 1 FAD). ), katombo (253 kg; 2 FADs), and rattan (734 kg; 1 FAD). Close relationship and influence Parameters that have the strongest relationship and influence on fluctuations in pelagic fish catches in purse seine fisheries in the Makassar Strait are salinity, dissolved oxygen and nitrate.